Quantitative determination of peroxide value in thermally oxidized palm olein by Fourier transform infrared spectroscopy - Setiowaty, G.; Che Man, Y.B.; Jinap, S.; Moh, M.H. (John Wiley & Sons, 2000)
A simple and rapid quantitative method to determine peroxide value (PV) of palm olein has been developed using transmittance Fourier transform (FT) IR spectroscopy. Palm olein was oxidized and blended with unoxidized palm olein to generate samples with PVs in the range 3.52-9.86. These samples were used in the calibration and validation steps. A calibration model based on partial least-squares analysis was constructed using the spectral and chemical data of the calibration set. Evaluation of the calibration model was carried out by cross-validation. The standard error of prediction and coefficient determination obtained from the cross-validation equation were 0.172 PV and 0.996, respectively. The standard deviation of the difference for reproducibility of the FTIR method was found to be better than that of the chemical method. The FTIR method would be suitable for PV determinations in the palm olein industry and takes an average of less than 2 min per sample.